Transvaginal retropubic sling systems: efficacy and patient acceptability - Moldovan CP; Marinone ME; Staack A (Dove Medical Press, 2015)
Christina P Moldovan,1 Michelle E Marinone,2 Andrea Staack3 1Department of Psychology, Loma Linda University, Loma Linda, California, United States of America; 2School of Medicine, Loma Linda University, Loma Linda, California, United States of America; 3Department of Urology, Loma Linda University Medical Center, Loma Linda, California, United States of America Abstract: Stress urinary incontinence is a common, disabling, and costly medical problem that affects approximately 50% of women with urinary incontinence. Suburethral retropubic slings have been developed as a minimally invasive and effective surgical option, and they have been used as a first-line treatment for stress urinary incontinence since 1995. However, complications including vaginal extrusion, erosion, pain, bleeding, infections, lower urinary tract symptoms, urinary retention, and incontinence have been reported with use of the slings. Several companies manufacture sling kits, and the sling kits vary with regard to the composition of the mesh and introducer needle. The aim of this review was to determine which sling kit was most effective for patients, had minimal reported side effects, and was best accepted by patients and surgeons. In a review of the literature, it was found that a total of 38 studies were published between 1995 and 2014 that reported on eight tension-free retropubic sling kits: SPARC, RetroArc, Align, Advantage, Lynx, Desara, Supris, and Gynecare TVT. The Gynecare TVT was the most cited sling kit; the second most cited was the SPARC. This review provides a summary of the studies that have examined positive and negative outcomes of the retropubic tension-free suburethral sling procedure using various sling kits. Overall, the results of the literature review indicated that data from comparisons of the available sling kits are insufficient to make an evidenced-based recommendation. Therefore, the decision regarding which sling kit is appropriate to use in surgery is determined by the medical provider’s preference, training, and past experience, and not by the patient. Keywords: stress urinary incontinence, retropubic sling kits, efficacy, outcome